ANALISIS PERBANDINGAN KESEHATAN PERUSAHAAN DITINJAU DARI RASIO KEUANGAN SEBELUM DAN SELAMA PANDEMI COVID-19 - Ayu Indira; Muhammad Riza Hafizi; Hasnita Hasnita (LP2M Universitas Bina Bangsa, 2023)
This study compares company health in financial ratios before and during the COVID-19pandemic. The ratios used in this study are Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), Total Asset Turnover (TATO) and Price Earning Ratio (PER). This research approach uses quantitative methods with comparative research types. The study population is the automotive sub-sector companies on the Indonesia Stock Exchange. The sample selection was carried out using a purposive sampling method so that 10 samples of automotive sub-sector companies were obtained in 2018-2021. Statistical analysis in this study were descriptive statistics, normality test, paired sample t-test, and Wilcoxon signed rank test. The results of this study indicate that there are significant differences between the health of companies before and during the COVID-19pandemic in 2018-2021 from the variables Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), and Price Earning Ratio (PER). There are differences, namely the Total Asset Turnover (TATO) variable before and during the 2018-2021 COVID-19pandemic. Because during the COVID-19pandemic, the value of Total Asset Turnover TATO decreased due to not maximizing people's purchasing power in the automotive market